Quantitative power loss analysis and optimisation in Nth‐order low‐voltage multilevel converters. Issue 7 (7th June 2019) - Petersen, Alexander; Stone, David A.; Foster, Martin P.; Davidson, Jonathan N.
Abstract : Focusing on cascaded H‐bridge converters for grid‐tie battery energy storage, a practical, analytical method is derived to evaluate the switching‐associated power loss in multilevel converters, evaluated from a number of sources of loss. This new method is then used to find performance trends in the use of converters of increasing order over a range of switching frequencies. This includes an experimental analysis into predicting the performance of MOSFET body diodes. Authors' analysis with this model shows that a multilevel converter can have lower losses than the equivalent single‐bridge, three‐level converter, particularly at higher switching frequencies, due to the availability of suitable switching devices. It also has interesting implications for enabling the use of cutting‐edge non‐silicon power switching devices to further improve potential efficiencies.